2021
DOI: 10.1111/nph.17357
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the components of triploid block and its fitness consequences in natural diploid–tetraploid contact zones of Arabidopsis arenosa

Abstract: Hybrid seed inviability (HSI) is an important mechanism of reproductive isolation and speciation. HSI varies in strength among populations of diploid species but it remains to be tested whether similar processes affect natural variation in HSI within ploidy-variable species (triploid block).Here we used extensive endosperm, seed and F 1 -hybrid phenotyping to explore HSI variation within a diploid-autotetraploid species. By leveraging 12 population pairs from three ploidy contact zones, we tested for the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 81 publications
0
29
1
Order By: Relevance
“…Support for this idea from well-studied systems like Arabidopsis and Capsella – both with the nuclear mode of endosperm development – has centered around the timing of endosperm cellularization. In maternal-excess crosses, precocious cellularization leads to reduced nuclear proliferation and seed size, whereas in paternal-excess crosses, delayed cellularization results in nuclei over-proliferation and larger seeds (Scott et al ., 1998; Pennington et al ., 2008; Rebernig et al ., 2015; Lafon-Placette et al ., 2017; Morgan et al ., 2021). Parent-of-origin effects on endosperm development have also been seen in crosses between species with cellular-type endosperms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this idea from well-studied systems like Arabidopsis and Capsella – both with the nuclear mode of endosperm development – has centered around the timing of endosperm cellularization. In maternal-excess crosses, precocious cellularization leads to reduced nuclear proliferation and seed size, whereas in paternal-excess crosses, delayed cellularization results in nuclei over-proliferation and larger seeds (Scott et al ., 1998; Pennington et al ., 2008; Rebernig et al ., 2015; Lafon-Placette et al ., 2017; Morgan et al ., 2021). Parent-of-origin effects on endosperm development have also been seen in crosses between species with cellular-type endosperms.…”
Section: Discussionmentioning
confidence: 99%
“…Most of what is known about the developmental phenotypes associated with hybrid seed inviability comes from crosses in Arabidopsis and other systems with nuclear-type endosperms (so called because the early endosperm forms a syncytium; Bushell et al ., 2003; Rebernig et al ., 2015; Floyd & Friedman, 2000), where the timing of cellularization seems to be a major determinant of nutrient acquisition and seed size (Garcia et al ., 2003; Luo et al ., 2005; Kang et al ., 2008; Hehenberger et al ., 2012). In interploidy crosses in these systems, endosperm cellularization is often precocious when the seed parent has higher ploidy and delayed when the pollen parent has higher ploidy, resulting in smaller or larger seeds, respectively (Scott et al ., 1998; Pennington et al ., 2008; Lu et al ., 2012; Morgan et al ., 2021). The fact that these same maternal-and paternal-excess effects on cellularization have been observed in crosses between species of the same ploidy in Arabidopsis and Capsella (Lafon-Placette et al ., 2017; Rebernig et al ., 2015; Lafon-Placette et al ., 2018) has been taken as evidence for parental conflict in nuclear-type endosperms.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis arenosa (Brassicaceae) is a diploid‐autotetraploid species with a well‐described evolutionary history of its lineages (see Figure 1), that has recently become a model system not only to study polyploid evolution (Bohutínská, Handrick, et al, 2021; Monnahan et al, 2019; Morgan, Čertner, et al, 2021; Morgan, White, et al, 2021), but also adaptation to extreme conditions (Bohutínská, Vlček, et al, 2021; Knotek et al, 2020; Konečná et al, 2021; Wos et al, 2021). Multiple studies have addressed the role of niche differentiation in the autopolyploid evolution of this system, however, reaching strikingly inconsistent outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…genes are expressed based on whether they are maternally or paternally derived), the balance of which allows development to proceed normally (Scott et al 1998; Köhler and Weinhofer-Molisch 2010). Much research using interploidy crosses has demonstrated that an overexpression of maternally expressed or paternally expressed genes results in canonical developmental defects across multiple plant systems and endosperm developmental programs (Scott et al 1998; Kradolfer et al 2013; Wolff et al 2015; Lafon-Placette and Köhler 2016; Lafon-Placette et al 2017; Morgan et al 2021). Strikingly, excess of maternal or paternal expression results in growth-repressive or growth-excessive phenotypes, reminiscent of predictions of parental conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, excess of maternal or paternal expression results in growth-repressive or growth-excessive phenotypes, reminiscent of predictions of parental conflict. If these endosperm defects are severe enough they can cause embryo death, and as such seed inviability is thought to be a crucial reproductive barrier between plants of different ploidy levels (often referred to as ‘Triploid Block’; (Comai 2005; Köhler et al 2010, 2021; Sutherland and Galloway 2017; Morgan et al 2021)).…”
Section: Introductionmentioning
confidence: 99%